The effect of educational program based on theory of planned behavior on health promotion and childbearing of minor thalassemia couples - Khadijeh Sarayloo; Zahra Behboodi Moghadam; Mohsen Saffari; Habibollah Esmaily; Khadijeh Mirzaii Najmabadi (Journal of Education and Health Promotion, 2019)
INTRODUCTION: It is essential to provide key information and support to every woman regarding pregnancy and childbirth to enable all women to make a fully informed decision regarding their choice of reproduction. The study aimed to find the impact of an educational program based on the Theory of Planned Behavior (TPB) on health promotion and childbearing of minor thalassemia couples. SUBJECTS AND METHODS: This study was quasi-experimental. A total of 70 women with minor thalassemia held in Minudasht health center were classified into two groups: study and control. The study group received the educational program based on TPB, and the control group only received the routine program. The data were collected using the TPB-based questionnaire at baseline and 3 months after the intervention. They were analyzed by Chi-square, Student's t-test, Wilcoxon test, and regression analysis through SPSS version 16. RESULTS: The mean (standard deviation) ages of the participants in the control and study group were 30.69 (6.20) and 31.08 (6.66), respectively. There were significant differences between the two groups (study vs. control) in terms of perceived behavioral control, intention, attitude, or childbearing behavior (P < 0.001). The change in fertility behaviors had a significant increase in the study group (62.8%) compared to the control group (2.9%) (P < 0.001). CONCLUSION: Based on the results, the TPB is an effective model to explain fertility intentions and behaviors in Iranian women with minor thalassemia; however, further researches are needed to generalize our findings to other people including healthy women.